The child as a medium. Breakdown and possible resurgence of children's agency in the era of pandemic. (November 2022) - Amadasi, Sara; Baraldi, Claudio
This paper deals with the unpredictable outbreak of the pandemic, explaining its impact on the education system, and with structural flexibility as a way to face unpredictability, based on the generalisability and coordination of manifestations of agency. The pandemic has enhanced a narrative of the child as a medium of learning, which undermines children's agency. The example of the research project CHILD-UP (Children Hybrid Integration: Learning Dialogue as a way of Upgrading policies of Participation) is used to show how children's agency and structural flexibility in classroom interactions can be supported and analysed.